Walking Together: Dynamics of Muslim Wives Dual Role in Rural Areas Pursuing Career and Household Responsibilities - Saiin, Asrizal; Firdaus, Firdaus; Yusuf, Maulana; Supani, Supani; Muchimah, Muchimah; Radiamoda, Anwar M. (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
The social reality today in rural areas, a wife works to help the family economy, besides having to do domestic tasks. The concept of gender does not prohibit a wife from working. However, this will be a problem if it creates gender inequality. This study aims to reveal the problem of fulfilling domestic duties for career wives in terms of gender perspective. This research is qualitative with the type of literature study, descriptive analytical method with based on a gender approach. The result of this study is that the career wife in fulfilling domestic duties in rural areas based on a gender perspective can be seen from the role that must be carried out. The wife's roles in a gender perspective are: a) mother's role, b) wife's role, c) social role, d) family's motivator. Getting many roles, apart from being a housewife and also having to work is not an easy thing for a wife. This role must be shared with the husband so that it can be balanced so as to create harmony in a household. A woman who already has a role as a mother, wife, member of the community and also has to play a role in the family, but the husband must help and support fully.